Manajemen Pemasaran Jasa Pendidikan dalam Meningkatkan Citra Lembaga Melalui Kegiatan Non Akademik di SMP IT Abu Bakar Yogyakarta - Zukhrufiana, Nazala Nur; Majidah, Rima (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2022)
This study examines problems related to marketing management of educational services in improving the image of Islamic educational institutions through non-academic activities, starting from the marketing strategy used, the impact of marketing management strategies on the image of educational institutions and the key to success. This type of research is a field research, which is qualitative descriptive. Data collection methods in this study are interviews, observation and documentation. The data analysis uses data flow model analysis, namely data reduction, data presentation and conclusion drawing. The validity of the data was tested by triangulation of sources and triangulation of techniques. The results of this study indicate that: First, the marketing management of educational services in improving the image of educational institutions through non academic activities is carried out by implementing marketing management strategies, namely: (1) Planning by establishing the vision, mission, and goals of education and then identifying the market, market segmentation and positioning, and product differentiation. (2) Organizing is carried out by dividing the existing tasks to educator resources. (3) Actuating, by implementing a planned program using a marketing mix strategy. Then the last one is (4) Controlling. Second, the marketing management of educational services at SMP IT Abu Bakar Yogyakarta is proven to have a positive impact in improving the image of Islamic educational institutions through non academic activities, including: (1) Increasing public trust. (2) The establishment of good cooperation between schools and parents as users of educational services. (3) The number of guests for comparative studies. Third, the keys to the success of marketing management of educational services in improving the image of Islamic educational institutions through non-academic activities at SMP IT Abu Bakar Yogyakarta are: (1) The products they have are quite varied. (2) The number of achievements in both the academic and non academic fields. (3) SMP IT Abu Bakar Yogyakarta strives to maintain good communication with users of educational services and (4) Adequate educational facilities.